Asikhulume! African Language for All, a Powerful Strategy for Spearheading Transformation and Improvement of the South African Education System - (:unkn) unknown (My University, 2025)
Almost twenty years after Bantu Education was repelled and fifteen years into democracy, the South African education system remains bedevilled by huge social inequalities. Language is part of that realm of inequality to the extent that the medium of instruction has become the hallmark of a school's social status. If this situation is allowed to continue, there is little hope that any change in this domain will be willingly accepted by the parents of those for whom such a change would be most beneficial, i.e. African learners whose mother-tongue is at odds with the ‘language of learning and teaching', pedagogically sound though it may be. Still, the failure rate among those remains unacceptably high. To overcome this seemingly untractable situation, I argue that mother-tongue education should be made available to all the speakers of any one of the 11 official South African languages, whatever the type of school they attend, and that passing an African indigenous language should become compulsory for all learners writing the senior certificate examination. Such measures could go a long way to trigger transformation in the education scene, and might even lead to a degree of racial and social integration, bringing about the long due transformation of the country.
Keywords: African Research